A system dynamic approach in human resource planning in oil and gas industry - Dina Diyana, Rastam Tan (2013)
This study deals with the factors that affecting the Human Resource Planning in Oil and Gas Industry. In this research study, a relationship between two factors such as Production Rate and Mobility Rate will be the change factors that can affect the outcome or output in this study as it related with the research objective of this research which is to study the factors affecting the Human Resource Planning. This research study will demonstrate the capability of the System dynamics modeling to model the human resource planning involving with some elements that can be as an important factors that can affect the planning of human resource in the oil and gas company. The developed causal loop diagrams are then will be translated into stock flow diagram model by inserting the data that can be calculated into each variables of Flow, Stock and Converter involved. The developed Stock Flow Diagram is then used to run themodel for further analysis which it can help in achieving the objective of this research study. In fact, this model can be implemented in various industry as well as it will help the Human resource Manager or Project Manager to forecast the actual workers needed to be hired to perform a task and achieved the goal or objective of the organization in terms of the production rate for example.